1982
DOI: 10.1128/iai.38.2.651-667.1982
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of experimental gingivitis in young adult humans

Abstract: From replicate trials of experimental gingivitis in four periodontally healthy subjects, 166 bacterial species and subspecies were detected among 3,034 randomly selected isolates from 96 samples. Of these bacteria, Actinomyces naeslundii (serotype III and phenotypically similar strains that were unreactive with available antisera), Actinomyces odontolyticus (serotype I and phenotypically similar strains that were unreactive with available antisera), Fusobacterium nucleatum, Lactobacillus species D-2, Streptoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
201
3
4

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(213 citation statements)
references
References 23 publications
5
201
3
4
Order By: Relevance
“…In this study, the ratio of anaerobes :aerobes increased significantly in the placebo group but not in the test group. Thus the plaque from the placebo group more closely resembled plaque associated with gingivitis (Moore et al 1982;. Also, after 3 weeks experimental gingivitis, plaque isolated from the test group contained lower numbers of Actinomyces species than plaque from the placebo group.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In this study, the ratio of anaerobes :aerobes increased significantly in the placebo group but not in the test group. Thus the plaque from the placebo group more closely resembled plaque associated with gingivitis (Moore et al 1982;. Also, after 3 weeks experimental gingivitis, plaque isolated from the test group contained lower numbers of Actinomyces species than plaque from the placebo group.…”
Section: Discussionmentioning
confidence: 80%
“…As there is some evidence that these bacteria can be correlated with the onset of gingivitis (Jordan et al 1972, Crawford et al 1978a, a reduction in numbers may be chnically significant. Moore et al (1982) correlated the onset of gingivitis with an increase in plaque complexity. At the end of this study plaque from the test group contained a greater spectrum of bacterial species than plaque from the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of microorganisms growing under anaerobic conditions and the total number of streptococci were calculated. Further, growth of Streptococcus sanguinis/oralis and Streptococcus salivarius, associated with good oral health 18 , mutans streptococci and lactobacilli, associated with dental caries 19 , Actinomyces spp., associated with root caries 20 , Fusobacterium nucleatum and Prevotella intermedia/nigrescens, associated with gingival inflammation 21 , Porphyromonas gingivalis and Aggregatibacter actinomycytemcomitans, associated with periodontitis 22 and Candida albicans, Staphylococcus aureus, enteric rods and enterococci, associated with mucosal infection 23 , was all analysed. The detection limit was 100 colony-forming units for all species except A. actinomycytemcomitans, where the detection limit was 10 colony-forming units.…”
Section: Microbial Sampling and Analysismentioning
confidence: 99%
“…exogenously secreted, end-product of Adinomyces species. Thus, the overgrowth of Actinomyix's such as that which occurs in gingivitis (Moore et al 1982) would be expected to enhance the observed colonization frequency and numerical density of Baclcroides species. Grenier et al (1986) demonstrated that Wolinella recia produced protohema that stimulated the growth of Bacleroides gingivalis and Bacleroides melaninogenicus.…”
mentioning
confidence: 99%